Answer:
The answer is: y = -1/2x - 7/2
Explanation:
Given points: (5, -6) and (-1, -3).
Solve for the slope:
m = (y - y1)/(x - x1)
m = -6 -(-3)/(5 - (-1))
m = -6 + 3/(5 + 1)
m = -3/6 = -1/2
Use the point slope form with point (-1, -3) and solve for y:
y - y1 = m(x - x1)
y - (-3) = -1/2(x - (-1))
y + 3 = -1/2(x + 1)
y + 3 = -1/2x - 1/2
y = -1/2x - 1/2 - 3
y = -1/2x -1/2 - 6/2
y = -1/2x - 7/2
Proof using poing (5, -6):
f(5) = -1/2(5) - 7/2
= -5/2 - 7/2
= -12/6 = -6, giving (5, -6)
Hope this helps! Have an awesome day!! :-)